2023
DOI: 10.1111/ene.16079
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of intravenous and subcutaneous immunoglobulin in chronic inflammatory demyelinating polyneuropathy: An observational study

Martin K. R. Svačina,
Anika Meißner,
Finja Schweitzer
et al.

Abstract: Background and purposeIt is not known whether the route of administration affects the mechanisms of action of therapeutic immunoglobulin in chronic inflammatory demyelinating polyneuropathy (CIDP). The aim of this study, therefore, was to compare the immunomodulatory effects of intravenous (IVIg) and subcutaneous immunoglobulin (SCIg) in patients with CIDP and in IVIg‐treated common variable immunodeficiency (CVID) patients.MethodsSerum and peripheral blood mononuclear cell samples were obtained from 30 CIDP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent study compared IVIg and SCIg treatments and found that they similarly impacted specific immune cells, but IVIg had a broader influence on serum cytokines than SCIg. 82 It is suggested that IVIg and SCIg have distinct pharmacokinetics, leading to different post-infusion cytokine patterns in CIDP patients. However, there were no therapeutically meaningful differences.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…A recent study compared IVIg and SCIg treatments and found that they similarly impacted specific immune cells, but IVIg had a broader influence on serum cytokines than SCIg. 82 It is suggested that IVIg and SCIg have distinct pharmacokinetics, leading to different post-infusion cytokine patterns in CIDP patients. However, there were no therapeutically meaningful differences.…”
Section: Treatment Strategiesmentioning
confidence: 99%